The Residues and Risk Assessment of Sulfonamides in Animal Products - Xiao-lei Zuo; Han Ai-yun (Journal of Food Quality)
Objective. To investigate and assess the risk of sulfonamide residues in livestock and poultry products in Shijiazhuang and determine the risk level of the dietary intake of sulfonamides, in order to provide the basis for the safety production, consumption, and safety supervision of livestock products. Methods. Totally, 1200 samples of livestock products were collected, and the samples were detected by high-performance liquid chromatography-tandem mass spectrometry. Combined with the data of Chinese residents’ dietary survey in 2015, a nonparametric probability assessment model was constructed to assess the risk of sulfonamides in the livestock and poultry products of Shijiazhuang residents by using the professional risk assessment software @Risk. Risk assessment of the consumption of sulfonamide veterinary drugs in livestock and poultry products of Shijiazhuang residents was conducted. Results. Of the 1200 main livestock products tested, 8 were found to have sulfonamide residues, which were mainly sulfadiazine residue, sulfadiazine, and sulfadimethoxy, with the detection rates of 0.17%, 0.25%, and 0.25%, respectively. The average residual concentrations were 0.66, 0.50, and 0.50 g/kg, respectively, which were lower than the national residue limit of China (100 μg/kg). The food safety index was 2.95 × 10−4, which was far less than 1. Conclusion. The risk of residual exposure to sulfonamides in livestock and poultry meat in Shijiazhuang is very low and is at a very safe level. However, it is still necessary to strengthen the supervision of animal products in order to reduce the residues of veterinary drugs in the human body.